2015 IEEE Global Communications Conference (GLOBECOM) 2014
DOI: 10.1109/glocom.2014.7416987
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of General Dual-Hop AF Systems over Rician Fading Links

Abstract: A unified performance analysis is presented for dualhop amplify-and-forward (AF) relaying systems operating over non-identically distributed Rician fading channels. A general, two-parameter AF relaying model is used to cover various AF relaying schemes, namely, variable-gain AF relaying, fixedgain AF relaying, and channel-assisted relaying, as well other unconventional schemes. Although, in some applications, systems operating over Rician fading links can be approximated and analyzed using equivalent systems o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…For Rician/Rician fading links, new analytical and asymptotic expressions for the OP, SER, and average capacity are derived as special cases considering variable‐gain relaying system with beamforming. In [29], Soliman et al concluded that dual‐hop relaying systems operating over Rician fading links have different diversity orders from those of the systems operating over the equivalent Nakagami‐ m fading links. The corresponding Nakagami‐ m and Rician parameters, m and K , were taken according to the equivalence notion presented in [24, eq.…”
Section: Special Casesmentioning
confidence: 99%
“…For Rician/Rician fading links, new analytical and asymptotic expressions for the OP, SER, and average capacity are derived as special cases considering variable‐gain relaying system with beamforming. In [29], Soliman et al concluded that dual‐hop relaying systems operating over Rician fading links have different diversity orders from those of the systems operating over the equivalent Nakagami‐ m fading links. The corresponding Nakagami‐ m and Rician parameters, m and K , were taken according to the equivalence notion presented in [24, eq.…”
Section: Special Casesmentioning
confidence: 99%
“…Many probability distributions are used to model the effects of fading on the received signal on mmWave links such as Nakagami‐ m , Fluctuating Two‐Rays, Rayleigh, and Rician distributions. The common distribution is used to model the mmWave channel is the Rician distribution . This distribution is described by Rician factor K , which is the ratio between the mean power of the line‐of‐sight (LOS) path and the mean power of the remaining non‐LOS paths .…”
Section: Introductionmentioning
confidence: 99%
“…The common distribution is used to model the mmWave channel is the Rician distribution. 6,[9][10][11] This distribution is described by Rician factor K, which is the ratio between the mean power of the line-of-sight (LOS) path and the mean power of the remaining non-LOS paths. 12 The Int J Commun Syst.…”
mentioning
confidence: 99%